How Students' Expectations Shape Their Quest for Purpose During College. Issue 1 (2nd January 2016) - Robinson, Jessica A.; Glanzer, Perry L.
Abstract : This article presents the findings of a 75-participant phenomenological study that examined the relationship between students' expectations of their university experience and their perception of purpose development. A clear dichotomy emerged between those who had a "holistic" mindset and understood their university as a place to develop a larger purpose and those who had an "instrumental" mindset and viewed their university solely as a place to develop skills to enhance a future career.